Design and performance of a power generating manual treadmill - Al-Talib, Ammar A. M.; Sarah ‘Atifah, Saruchi; Cik Suhana, Hassan; Nor Fazilah, Abdullah; Ain Atiqa, Mustapha; Jelban, Ahmad (ALife Robotics Corporation Ltd, 2024)
Treadmills are one of the most popular training equipment in the gym and at home. The working principle of treadmills is by moving the belt with the human knee bending, which creates mechanical energy to turn the belt. A gear or pulley and belt system connects to the generator along the axel line of the rolling bars. The power generated by the DC generator is stored in a battery pack and could be used to charge phones or other equipment. It has been found that treadmills can provide an efficiency of 95% when the DC motor is used and 92% when the AC motor is used. The main objective of this study is to design and fabricate a powder-generating manual treadmill and to analyze the performance of the system under different operation conditions.